2017
DOI: 10.1002/hep.29523
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome driven liver injury and fibrosis: Roles of IL‐17 and TNF in mice

Abstract: Our study uncovers key roles for TNF and, to a lesser extent, IL-17 as mediators of liver inflammation and fibrosis induced by constitutive NLRP3 inflammasome activation in myeloid-derived cells. These findings may lead to therapeutic strategies aimed at halting the progression of liver injury and fibrogenesis in various liver pathogeneses driven by NLRP3 activation. (Hepatology 2017).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
178
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(187 citation statements)
references
References 52 publications
8
178
0
1
Order By: Relevance
“…Here, modulation of potent NF‐κB mediators (IL‐1α) and NLRP3 inflarnmasome constituents (IL‐1β, IL‐18) in serum at weaning in OFS offspring compared with HFS offspring suggests that they have a reduction in systemic inflammation, in some cases to a level similar to offspring of lean dams, during a key developmental period. The increased serum MIP‐2/CXCL2 and LIX/CXCL5 at 11 wk in HFS offspring provide further evidence of altered NLRP3‐associated inflammation, as they are associated with inflarnmasome activated‐neutrophil recruitment, and liver mRNA for both of these analytes are increased in NLRP3 knockin mice along with severe inflammation characteristic of progressive NAFLD (47, 48). The increase in IP‐10/CXCL10 in HFS females at 24 wk, and its correlation with percent body fat, again suggests a higher degree of NLPR3 activation in HFS offspring (49).…”
Section: Discussionmentioning
confidence: 92%
“…Here, modulation of potent NF‐κB mediators (IL‐1α) and NLRP3 inflarnmasome constituents (IL‐1β, IL‐18) in serum at weaning in OFS offspring compared with HFS offspring suggests that they have a reduction in systemic inflammation, in some cases to a level similar to offspring of lean dams, during a key developmental period. The increased serum MIP‐2/CXCL2 and LIX/CXCL5 at 11 wk in HFS offspring provide further evidence of altered NLRP3‐associated inflammation, as they are associated with inflarnmasome activated‐neutrophil recruitment, and liver mRNA for both of these analytes are increased in NLRP3 knockin mice along with severe inflammation characteristic of progressive NAFLD (47, 48). The increase in IP‐10/CXCL10 in HFS females at 24 wk, and its correlation with percent body fat, again suggests a higher degree of NLPR3 activation in HFS offspring (49).…”
Section: Discussionmentioning
confidence: 92%
“…Exploring cellular and molecular mechanisms that are responsible for LF development may lead to the identification of antifibrotic approaches that could help improve the treatment and prognosis of CLDs . Growing evidence supports a central role of NLRP3 activation and downstream effectors, such as Casp‐1 activation and IL‐1β signaling in the development of LF . It has been shown that level of Nlrp3 expression, among other inflammasomes, is augmented during experimental LF .…”
Section: Discussionmentioning
confidence: 99%
“…(21) Growing evidence supports a central role of NLRP3 activation and downstream effectors, such as Casp-1 activation and IL-1β signaling in the development of LF. (7,(11)(12)(13)22) It has been shown that level of Nlrp3 expression, among other inflammasomes, is augmented during experimental LF. (23) To date, there are only a few studies elucidating different stimuli that can trigger HSC activation and subsequent up-regulation of fibrotic markers along with activation of the NLRP3 inflammasome in both LX-2 cells, an immortalized human stellate cell line, and murine primary HSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wree et al previously described the ability of the NLRP3 inflammasome to generate spontaneous liver inflammation, hepatocyte death by pyroptosis, and fibrosis in studies employing transgenic mice with constitutive NLRP3 activation globally or conditionally in myeloid cells. In a continuation of this work in this issue of H epatology , they further investigated the mechanism by which NLRP3 drives hepatic inflammation and fibrosis . They hypothesized that NLRP3 inflammasome effects are mediated not only by inflammasome‐produced IL‐1β, but also by the inflammasome‐independent cytokines tumor necrosis factor (TNF) and IL‐17, which have known roles in liver injury and fibrosis.…”
mentioning
confidence: 99%